2021
DOI: 10.1007/s10040-021-02387-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the subsurface urban heat island and its sources in the Milan city area, Italy

Abstract: Urban areas are major contributors to the alteration of the local atmospheric and groundwater environment. The impact of such changes on the groundwater thermal regime is documented worldwide by elevated groundwater temperature in city centers with respect to the surrounding rural areas. This study investigates the subsurface urban heat island (SUHI) in the aquifers beneath the Milan city area in northern Italy, and assesses the natural and anthropogenic controls on groundwater temperatures within the urban ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Studies that report urban underground temperature over time are extremely rare and typically only comprise few years. Especially in studies covering less than five years, extreme temperature rises that locally exceed +2 K dec −1 (per decade) are reported [32,40,43], while also average temperature rises are above +0.5 K dec −1 [23,40,43]. In many places urban temperature rise more than doubles the expected surface warming in response to climate change [22,60].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that report urban underground temperature over time are extremely rare and typically only comprise few years. Especially in studies covering less than five years, extreme temperature rises that locally exceed +2 K dec −1 (per decade) are reported [32,40,43], while also average temperature rises are above +0.5 K dec −1 [23,40,43]. In many places urban temperature rise more than doubles the expected surface warming in response to climate change [22,60].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focus on obtaining data on GWT from satellite data with a designated LST [16]. Many studies based on point measurement data also interpolate data in order to obtain groundwater temperatures for the IOP Publishing doi:10.1088/1755-1315/1189/1/012028 13 analysed areas [22,54,55], with particular emphasis on the Kriging method [18,27,56]. The spatial distribution of the SSUHI phenomenon in the above-mentioned studies is similar to the distribution obtained in Wrocław.…”
Section: Discussionmentioning
confidence: 99%
“…Much research related to SSUHI is aimed at determining the geothermal energy potential for a given urban area [4][5][6], due to the ever-growing demand for energy, as well as the growing awareness of ecology. Identification of Subsurface Urban Heat Island was done both by satellite methods [16,25] and by in-situ measurements [22,26,27]. The conducted research has shown an increase in temperature below the city's surface by 2-8 °C in different parts of the world [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best results were obtained using the Ordinary Kriging method. In other studies, interpolation methods based on point measurement data were also used to obtain groundwater temperatures for the analyzed areas [46,47], with particular emphasis on the kriging method [48,49].…”
Section: Introductionmentioning
confidence: 99%